A TaqMan Real-Time PCR Assay for Detection and Quantification of Sporisorium scitamineum in Sugarcane - Yachun Su; Shanshan Wang; Jinlong Guo; Bantong Xue; Liping Xu; Youxiong Que (The Scientific World Journal)
Sporisorium scitamineum is a fungal smut pathogen epidemic in sugarcane producing areas. Early detection and proper identification of the smut are an essential requirement in its management practice. In this study, we developed a TaqMan real-time PCR assay using specific primers (bEQ-F/bEQ-R) and a TaqMan probe (bEQ-P) which were designed based on the bE (b East mating type) gene (Genbank Accession no. U61290.1). This method was more sensitive (a detection limit of 10 ag pbE DNA and 0.8 ng sugarcane genomic DNA) than that of conventional PCR (10 fg and 100 ng, resp.). Reliability was demonstrated through the positive detection of samples collected from artificially inoculated sugarcane plantlets (FN40). This assay was capable of detecting the smut pathogen at the initial stage (12 h) of infection and suitable for inspection of sugarcane pathogen-free seed cane and seedlings. Furthermore, quantification of pathogen was verified in pathogen-challenged buds in different sugarcane genotypes, which suggested its feasibility for evaluation of smut resistance in different sugarcane genotypes. Taken together, this novel assay can be used as a diagnostic tool for sensitive, accurate, fast, and quantitative detection of the smut pathogen especially for asymptomatic seed cane or plants and evaluation of smut resistance of sugarcane genotypes.